Factors Related To The Prevention Of Filariasis In Pasaman Barat - Dt Mangguang, Masrizal; Kusnanto, Hari; Lazuardi, Luthan (JOURNAL OF HEALTHCARE TECHNOLOGY AND MEDICINE, 2015)
The purpose of this study is to know the factors that relate to the prevention of filariasis in West Pasaman 2014.This research uses a cross sectional design. The sample size in this study is based on a minimum provision of finger blood survey study of 500 samples. Processing data using univariate, bivariate and mulivariat with statistical test Chi-Square.The factors associated with the prevention of filariasis, jobs at risk (PR = 1.280, 95% CI: 1.034 - 1.585) health education (PR = 1,545, CI 95% : 1,153-2,070) , socio-economic level (PR = 1.275, 95% CI: 1.049 - 1.550) and the factors that are not related, which is the level of education (PR = 1.107, 95% CI: 0.830 - 1.477), the level of knowledge (PR = 1.026, 95% CI: 0.048 - 1.240), attitude (PR = 0.962, 95% CI: 0.797 - 1.162), as well as the role of the community leaders (PR = 0.908, 95% CI: 0.746 - 1.105).Health education is the most dominant factor in the prevention of filariasis. That health promotion programs should be carried out regularly by health workers by improving communication, information, education and providing health education with the goal to improve disease prevention measures filariasis.